The influence of information and communication technology in the science of Qirā’āt - Fatah Yasin, Raudlotul Firdaus; Zulkifli, Zati Syahmeena (2019)
Information and Communication Technology (ICT) is the most significant assistance in education, and it becomes more accessible to the way of learning in the present world where ICT tools provide adequate support for the Science of Qirā’āt among the students or learners.